Responsabilidade ambiental nas pequenas propriedades certificadas pelo programa Certifica Minas Café - PRADO, Rogério Ramos do (2018)
The certification of coffee is of fundamental importance in guaranteeing a sustainable coffee cultivation, since it directs the coffee grower in the search for rational agricultural practices, with environmental responsibility and administrative management. The certification of coffee is aimed at guaranteeing a product of quality and traceable origin, registering the entire coffee production process, from the implantation to the processing. In order to guarantee the development of sustainable agriculture in Brazil, a legislative effort was made to consolidate legislation on environmental education and the development of certification processes aimed at a cultural change of the population. The National Environmental Education Program guarantees the national guidelines for an effective and continuous environmental education in the country. The Certifica Minas Café certification program, designed by the State Government of Minas Gerais, has as main objective the implementation of good production practices in the properties in order to increase the visibility and competitiveness of coffee in the national and international markets. The aim of this study was to evaluate the influence of the Certifica Minas Café program on the environmental responsibility of small coffee growers, analyzing the results of evaluations of 27 (twenty seven) environmental liability standards in the biennium 2015 and 2016, from 175 (one hundred and seventy and five) small properties of 8 (eight) regions, with an area of less than 30 ha. Legislation related to water legislation and conservation had a strong influence on the process of environmental responsibility and, consequently, on the environmental education of coffee growers. In 2016, standards related to soil and water conservation showed better results. Patrocínio, Varginha and Juiz de Fora were the regions with the best results, as well as the properties with areas between 25 and 30 ha. The Certifica Minas Café Program contributes to the effective accomplishment of the mission of the National Environmental Education Program, as well as to social and environmental sustainability and environmental responsibility.